Critical Stylistics Study Of Serial Killer Characters and Their Representations in The Fictional Series Criminal Minds Evolution - Kusumaningrum, Ayu; Supeno, Supeno; Hanifah, Nani (INFERENCE: Journal of English Language Teaching, 2024)
This research aims to analyze how the characters and representations of serial killers in fictional series are depicted. The data source used in this research is dialogue transcripts from the fictional series Criminal Minds Evolution, which consists of ten episodes. The research was conducted using the observation method. Data analysis uses Critical Stylistics Analysis tools specifically for Naming and Describing, Representing Actions/Events/States, and Equating and Contrasting tools. The research results obtained the following conclusions: 1) The author tends to use Naming, Material Action Intentional, Mental Cognition, and Equating tools in depicting the characters of serial killers. 2) The author represents serial killers as males, citizens of the United States, in of a various range of ages, have families, have psychopathic traits, are organized and methodical, have a variety of social and occupational statuses, and have a motive for revenge.